Tata ABC workbook - El far, Amr Gamal; El Sawy, Shereen; Othman, Reem ([Cairo] author, 2025)
Join a delightful adventure as a dad teaches his baby the alphabet in the most engaging way- by feeding him letters and sounds! this innovative phonics resource brings literacy to life through playful interactions, ensuring that learning is both fun and effective
Linguistic notions
Keywords: English language